SECRET KILLERS “AFTER WIKILEAKS”: MAPPING, EVOLUTIONS, AND TAXONOMY OF RADICAL LEAKING - Heemsbergen, Luke (AoIR Selected Papers of Internet Research, 2018)
This paper is concerned with mapping the socio-material ecosystems of online leaks projects that followed WikiLeaks. The period of initial popularisation/infamy of WikiLeaks (2006-2015) correlates with an emergence of over 90 less-known radical online disclosure projects designed to ""Kill Secrets"" (Greenberg 2012). We offer the first systematic study of the decentralised and widely disparate ecosystem of leaks projects to build a taxonomy of leaks sites (n:94) from various observable socio-technical vectors. Affordances tied to user and technical practice, vectors such as self-identified thematic focus (issue, region, etc.), and measures of publication efficacy for each site are all open coded to discern patterns and clusters of practice. Analysis then shifts to mapping of visible interrelationships between sites via social network analysis (SNA) for further insight to the ecology of leaks sites. Taxonomy over typology signals observing material practice without predetermined ideal type, and normative links to agonistic democratic theory. At a macro level our findings suggest, an ecology of leaks sites blossomed and died, with only a handful of sites remaining online, or having ever actually functioned. Micro to Meso analysis of practices show how leaks sites’ socio-technical materiality helps shape both efficacy and normative goals, from which unique and sometimes agonistic normative governmental functions can be inferred. Discussion of findings then critically assess how digital leaks served (and severed) ties to already problematic equations of ’transparency’ and democracy from a frame of agonistic and algorithmic government practices (Heemsbergen, 2016; Ananny and Crawford, 2016) and suggest tentative paths forward.